2018
DOI: 10.1021/acs.jpcb.7b10233
|View full text |Cite
|
Sign up to set email alerts
|

Energetics Underlying Twist Polymorphisms in Amyloid Fibrils

Abstract: Amyloid fibrils are highly ordered protein aggregates associated with more than 40 human diseases. The exact conditions under which the fibrils are grown determine many types of reported fibril polymorphism, including different twist patterns. Twist-based polymorphs display unique mechanical properties in vitro, and the relevance of twist polymorphism in amyloid diseases has been suggested. We present transmission electron microscopy images of Aβ42-derived (amyloid β) fibrils, which are associated with Alzheim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 95 publications
0
43
0
Order By: Relevance
“…This finding is credited to the sensitivity of EPR measurements to not only static structure, but also backbone and side chain dynamics. Side chain interactions in the β-sheet have been shown to be a determining factor of fibril twist 25,26 , a feature that is both distinguishing and most recognizable for different fibril polymorphs. While backbone hydrogen bonds always favor flat β-sheets, side chain interactions favor twisted β structures 37 .…”
Section: Scientific Reports |mentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is credited to the sensitivity of EPR measurements to not only static structure, but also backbone and side chain dynamics. Side chain interactions in the β-sheet have been shown to be a determining factor of fibril twist 25,26 , a feature that is both distinguishing and most recognizable for different fibril polymorphs. While backbone hydrogen bonds always favor flat β-sheets, side chain interactions favor twisted β structures 37 .…”
Section: Scientific Reports |mentioning
confidence: 99%
“…EPR data further revealed that side chains are more tightly packed in agitated Aβ40 fibrils than in quiescent Aβ40 fibrils. The strength of side chain packing interactions may determine the degree of β-sheet twist 25,26 , a distinguishing feature of some Aβ fibril polymorphs.…”
mentioning
confidence: 99%
“…Previous molecular dynamics (MD) simulations of fragments of amyloidogenic protein sequences (Sup35) have suggested that changes in fibril twisting (cross-over distance) may be due to different charge interactions at the protein's N-and C-termini (80,81). Specifically, with a negative charge at the C-terminus, model proteins adopted the more energetically favorable twisting conformation in MD simulations compared to the fibrils with no cross-over distance, which were less energetically favored (81). These simulation results may explain why the accessible negative surface charge of SBA-15 favors the formation of λ and μ fibrils compared to the ε fibrils that were highly represented in the control, SBA-PEG, and SiMP samples.…”
Section: Discussionmentioning
confidence: 99%
“…MD simulation of the αSyn amyloids demonstrated that all the β-sheets incessantly moved in a vibratory manner in narrow spaces, except for β1 and β2 which tended to freely twist and fan ( Supplementary Movie ). Considering the intrinsic twisting tendency [43], it is conceivable that the other β-sheets also share the tendency to twist like β1 and β2. Although they are not allowed to twist freely due to the compact packaging in the Greek-key conformation, even small twists can cause differences in the distances of β-sheets between on the Chain-A side and on the Chain-J side, and consequently differences in structural stabilities because hydrogen bonds or hydrophobic effects are greatly affected by the distances.…”
Section: Asymmetry Between the Chain-a And The Chain-j Sides Of The Smentioning
confidence: 99%
“…Given the existence of hydrogen bonds and hydrophobic effects between β3, β5 and β7 as revealed by the MD simulation, alterations in those interactions seem the most likely mechanism of the remote effects. In addition, the intrinsic twisting tendency of β-sheets could modulate the interactions because those properties of β-sheets affect each other [43]. The extra inter-layer hydrogen bonds of homo-A53T amyloid between Thr53 and Gly73 and/or Val74 suggest more intimate β3-β5 interactions ( Fig 3 ), which also explain the alterations of β-sheet propensities in the residues of β5.…”
Section: Remote Effects Of the Mutationsmentioning
confidence: 99%